Preparation method and application of water-soluble efficient luminous lanthanide complex with multiple hydrogen bond sites
By designing water-soluble lanthanide complexes with multiple hydrogen bond sites, the problem of poor luminescence performance of rare earth complexes in water is solved, and efficient fluorescence detection of 5-HIAA is achieved, and a carcinoid marker is provided effective biosensor.
Patent Information
- Application Number
- CN202411341647.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
Existing rare earth complexes cannot have high optical properties and water solubility at the same time, and it is difficult to effectively detect the carcinoid marker 5-HIAA in water.
A water-soluble, highly efficient luminescent lanthanide complex with multiple hydrogen bond sites was designed, and Eu-DPA was formed by dissolving rare earth salts in dimethylformamide and reacting with 2,6-pyridine dicarboxylic acid. The complex is treated with an ultrasonic two-dimensional material stripper to form a transparent solution, achieving efficient luminescence and stability in water.
Ultra-sensitive and highly selective fluorescence detection for 5-HIAA is achieved, with the lower detection limit reaching 1.46μM, which can effectively distinguish healthy people from patients in water, plasma and urine, and provides a new biological detection tool.
Smart Images

Figure CN119219555A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a lanthanide complex and application thereof. Background Art
[0002] Carcinoid tumors (apud cell tumors) are a type of tumor that can produce polypeptide or peptide hormones. These tumors work by increasing the concentration of cyclic adenosine monophosphate and secreting serotonin 5-hydroxytryptamine (5-HT) with strong physiological activity. After metabolism, 5-HT is mainly decomposed in the liver, and the product 5-hydroxyindoleacetic acid (5-HIAA) is excreted through urine. 5-HIAA is the main metabolite of 5-HT and is often detected in plasma, urine and cerebrospinal fluid. Its abnormal concentration usually indicates the presence of carcinoid tumors. In addition, the concentration of 5-HIAA is also associated with a variety of health conditions such as hypertension, migraine and Tourette syndrome. However, traditional chromatography-based detection techniques require expensive instruments and complex pretreatment, which is not only time-consuming but also produces solvents with harmful environmental effects. Therefore, the development of a simple, rapid, economical and environmentally friendly technology for real-time monitoring of 5-HIAA has important clinical significance and can effectively help prevent and diagnose carcinoid tumors at an early stage.
[0003] Rare earth complexes, as excellent fluorescent emitters in the biomedical field, have the characteristics of strong light absorption, high color purity, brightness and long luminescence lifetime. A variety of complexes have been designed whose effects can be adjusted by functional groups on the ligands. However, most rare earth complexes have poor water solubility and are easily quenched in water, and usually require poorly dispersed suspensions, which limits their possibility of directly detecting 5-HIAA through aqueous solutions. Considering the potential research value of water-soluble rare earth complexes in detecting 5-HIAA in biological fluids, it is particularly important to design a water-soluble and well-dispersed probe.
[0004] The groups of ligands usually contain hydrophilic and hydrophobic components, which affect their solubility in water. In addition, ligands can be classified as hard bases or soft bases according to their reaction characteristics. Since rare earth ions are hard acids, they react strongly with hard base ligands containing oxygen or fluorine, but react weakly with soft base ligands containing sulfur or nitrogen, resulting in poor stability of these complexes in water. In aqueous solution, water molecules as oxygen-containing ligands strongly bind to rare earth ions, while soft base ligands cannot replace water molecules due to weak interaction, resulting in the complexes being prone to fluorescence quenching in water. However, these complexes can emit light normally in non-aqueous solvents. In addition, a major challenge is how to reduce high-frequency OH bond vibration coupling in water, which causes the luminescence of Ln complexes to be weakened through non-radiative transitions. Therefore, the design of new Ln complexes requires the use of appropriate ligands to shield the interaction between Ln ions and OH groups. Although a variety of Ln complexes have been developed, it is difficult to achieve good water solubility and excellent luminescence properties at the same time. This suggests that it is necessary to develop novel Ln complexes with high optical properties and water solubility, which are expected to become valuable fluorescent bioassay tools. Summary of the invention
[0005] The present invention aims to solve the problem that existing rare earth complexes cannot have both high optical properties and water solubility, and further provide a preparation method and application of a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites.
[0006] A method for preparing a water-soluble, highly efficient, luminescent lanthanide complex having multiple hydrogen bonding sites is carried out according to the following steps:
[0007] 1. dissolving a rare earth salt in dimethylformamide to obtain a metal salt solution;
[0008] The rare earth salt is EuCl 3 6H 2 O、TbCl 3 6H 2 O, YbCl 3 6H 2 O、NdCl 3 6H 2 O or ErCl 3 6H 2 O;
[0009] 2. Dissolve 2,6-pyridinedicarboxylic acid in dimethylformamide to obtain 2,6-H 2 dpa solution;
[0010] 3. 2,6-H 2The dpa solution is added to the metal salt solution to obtain a reaction system. The reaction system is heated to react under stirring conditions, and then the product is filtered under reduced pressure, washed and dried to obtain a dried solid. Water is added to the dried solid, and then it is treated with an ultrasonic two-dimensional material stripper until a transparent solution is formed. Finally, it is freeze-dried to obtain a water-soluble, high-efficiency luminescent lanthanide complex with multiple hydrogen bonding sites.
[0011] Application of a water-soluble, highly efficient luminescent lanthanide complex with multiple hydrogen bonding sites as a luminescent sensor for the carcinoid marker 5-HIAA.
[0012] The beneficial effects of the present invention are:
[0013] The present invention successfully designed a water-soluble lanthanide complex with rare earth salt as EuCl 3 6H 2 Taking Eu-DPA as an example, the prepared water-soluble and highly luminescent lanthanide complex Eu-DPA with multiple hydrogen bonding sites has a solubility of 14.03g / 100g in water and highly luminescent in water (the quantum efficiency reaches 93.08% in 1g / L aqueous solution, and the lifetime is 2.062ms). It is used as a fluorescent probe to achieve ultra-sensitive and highly selective fluorescence detection of the carcinoid marker 5-hydroxyindoleacetic acid (5-HIAA) in water, plasma and urine. The water solubility of Eu-DPA is due to the hydrogen bonds formed between water molecules, which has been confirmed by theoretical calculations. Eu-DPA shows obvious fluorescence quenching phenomenon for 5-HIAA, and the shift of FTIR absorption peak and 1The results of H NMR titration all proved that intermolecular hydrogen bonds were formed between Eu-DPA and 5-HIAA. In addition, the results of DLS dynamic light scattering showed that hydrogen bonds enhanced the assembly effect between Eu-DPA and 5-HIAA. The unsaturated pyridine carboxylic acid oxygen in Eu-DPA formed electrostatic interactions with the hydroxyl and amino groups in 5-HIAA through intermolecular hydrogen bonds. These hydrogen bonds acted as "bridges" to form a charge transfer channel between Eu-DPA and 5-HIAA. Theoretical calculations further confirmed that multiple intermolecular hydrogen bonds could be formed, resulting in a synergistic effect. Using TAS and TRES techniques, the energy transfer pathway was analyzed, and it was verified that the fluorescence quenching mechanism was mainly that 5-HIAA blocked the energy transfer from the ligand to the rare earth. In addition, other water-soluble lanthanide complexes that emit light in the visible and near-infrared regions were synthesized. These complexes can be completely dissolved in water while maintaining good luminescence intensity. In order to better realize the application of actual in vivo detection, 5-HIAA was tested in urine samples, and good detection effects were obtained, with a detection limit of 1.46μM. In actual sample testing, the sensor can clearly distinguish between healthy people and sick people. The water-soluble lanthanide complexes developed in the present invention and the linkage of their multiple hydrogen bonds provide a new approach for the development of lanthanide complex fluorescent materials in the field of biological detection, and also provide important scientific support for future in vivo detection and cancer marker analysis, which is of great significance for applications in the fields of biomedicine and clinical diagnosis. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Schematic diagram of the Eu-DPA structure;
[0015] Figure 2 is the distance between Eu-DPA and water to form intermolecular hydrogen bonds. In the figure, the green ball is Eu, the gray ball is C, the red ball is O, the white ball is H, and the blue ball is N;
[0016] Figure 3 Microscope and SEM images of Eu-DPA and Eu-DPA-1;
[0017] Figure 4 is the dissolution time of Eu-DPA aqueous solution with different concentrations;
[0018] Figure 5 is the dynamic light scattering particle size distribution of Eu-DPA-1 aqueous solution;
[0019] Figure 6 Comparison of the Tyndall effect of Eu-DPA-1 aqueous solution and Eu-DPA aqueous solution after standing for 10 hours, a is Eu-DPA, b is Eu-DPA-1;
[0020] Figure 7The figure is a comparison of the luminescence intensity of Eu-DPA-1 aqueous solution and Eu-DPA aqueous solution before and after standing for 10 hours under ultraviolet light;
[0021] Figure 8 This is a stability comparison chart of Eu-DPA aqueous solution after standing for 3 months under ultraviolet light;
[0022] Fig. 9 1H NMR of Eu-DPA and Eu-DPA-1 in deuterated water;
[0023] Fig.10 is the X-ray diffraction pattern of Eu-DPA;
[0024] Fig.11 is the infrared spectrum of Eu-DPA;
[0025] Fig.12 XRD comparison diagrams of Eu-DPA-1, Eu-DPA, and Eu-DPA freeze-dried after standing in water for 3 months;
[0026] Fig.13 This is a stability comparison chart of Eu-DPA after heating;
[0027] Fig.14 The absorption spectrum, excitation spectrum and emission spectrum of Eu-DPA aqueous solution with a concentration of 1 g / L under fluorescence irradiation, a is the emission spectrum, b is the absorption spectrum, and c is the excitation spectrum;
[0028] Fig.15 is the quantum efficiency diagram of Eu-DPA aqueous solution;
[0029] Fig.16 is the fluorescence lifetime diagram of Eu-DPA aqueous solution;
[0030] Fig.17 Comparison diagram of Eu-DPA and Eu-DPA-1 under sunlight and ultraviolet irradiation, a) Eu-DPA and its aqueous solution (concentration of 1g / L), Eu-DPA-1 and its aqueous solution (concentration of 1g / L), b) Eu-DPA aqueous solution of different concentrations (concentration 0.1g / L to 3g / L), c) Luminescence comparison of Eu-DPA-1 aqueous solution (concentration of 1g / L) and Eu-DPA aqueous solution (concentration of 1g / L) before and after dialysis bag filtration under ultraviolet lamp (wavelength of 365nm, power of 30mw) irradiation (dashed box is a photo of the real sample), d) Photo comparison of Eu complex aqueous solution (concentration of 1g / L) under sunlight and ultraviolet irradiation before and after dialysis bag filtration;
[0031] Fig.18The physical pictures of Tb-DPA, Yb-DPA, Nd-DPA, Er-DPA and their aqueous solutions prepared in Example 2;
[0032] Fig.19 Schematic diagram of the process of detecting 5-HIAA by Eu-DPA;
[0033] Fig. 20 The detection capability of Eu-DPA for 5-HIAA, a is the detection picture, b is the actual picture;
[0034] Fig.21 This is the CIE chromaticity analysis diagram of Eu-DPA added with 5-HIAA;
[0035] Fig. 22 5-HIAA in H at room temperature 2 The quenching effect of O on Eu-DPA, a is the concentration dependence curve, b is the Ksv curve;
[0036] Fig.23 The quenching effect of 5-HIAA on Eu-DPA in urine at room temperature, a is the concentration dependence curve, b is the Ksv curve;
[0037] Fig.24 The quenching effect of 5-HIAA on Eu-DPA in serum at room temperature, a is the concentration dependence curve, b is the Ksv curve;
[0038] Fig.25 Schematic diagram of biological detection of carcinoid markers using different rare earth complexes (Ln-DPA);
[0039] Fig.26 The changes in fluorescence intensity of 5-HIAA detected by different rare earth complexes prepared in Example 2 (Ln-DPA), f) Yb-DPA, j) Nd-DPA, h) Er-DPA;
[0040] Fig. 27 For the anti-interference test and real urine testing, a) normal and pathological ranges corresponding to different 5-HIAA concentrations in real urine testing, b) testing of each substance, c) the ability of Eu-DPA to detect 5-HIAA in the presence of interferences, d) real urine testing of normal subjects and carcinoid patients;
[0041] Fig.28 Schematic diagram of hydrogen bonding interaction between Eu-DPA and 5-HIAA;
[0042] Fig.29 This is a point comparison diagram of Eu-DPA and Eu-DPA+5-HIAA;
[0043] Fig.30The hydrogen bonding in the system is demonstrated in Figure 2. b) The gradual addition of 5-HIAA to Eu-DPA 1 HNMR graph, (1) 8 mg Eu-DPA + 2 mg 5-HIAA, (2) 8 mg Eu-DPA + 4 mg 5-HIAA, (3) 8 mg Eu-DPA + 6 mg 5-HIAA, (4) 8 mg Eu-DPA + 8 mg 5-HIAA, (5) 8 mg Eu-DPA + 10 mg 5-HIAA, c) FT-IR spectrum of dynamic light scattering particle size distribution of Eu-DPA + 5-HIAA, d) DLS test of 5-HIAA and 1 mg Eu-DPA + 1 mg 5-HIAA;
[0044] Fig.31 XPS graphs of 5-HIAAEu-DPA, 5-HIAA and Eu-DPA+5-HIAA, e) O 1s spectrum; f) N 1s spectrum; g) Eu 4d spectrum;
[0045] Fig.32 Theoretical calculation diagrams, h) electrostatic potential of Eu-DPA and 5-HIAA, i) hydrogen bond distance between DPA and 5-HIAA, j) dihedral angle change of Eu-DPA after adding 5-HIAA;
[0046] Fig.33 The detection ability of Eu-DPA for 5-HIAA under neutral, acidic and alkaline conditions is shown in Figure 1. a is Eu-DPA aqueous solution, b is neutral environment, c is acidic environment, and d is alkaline environment.
[0047] Fig.34 It is the quenching effect diagram of Eu-DPA and Eu-DPA+indene;
[0048] Fig.35 It is the fluorescence intensity diagram of Eu-DPA and Eu-DPA+5-HIAA;
[0049] Fig.36 It is the fluorescence lifetime diagram of Eu-DPA and Eu-DPA+5-HIAA;
[0050] Fig.37 The structural diagrams of Gd-DPA and Eu-DPA;
[0051] Fig.38Mechanism analysis diagram, a) time-resolved fluorescence spectrum of Gd-DPA, b) time-resolved fluorescence spectrum of Eu-DPA, c) time-resolved fluorescence spectrum of Eu-DPA+5-HIAA, d) HOMO and LUMO of Eu-DPA and Eu-DPA+5-HIAA, e) femtosecond TA contour diagram of Eu-DPA, f) femtosecond TA contour diagram of Eu-DPA+5-HIAA, g) ΔEu-DPA absorbance change; h) ΔEu-DPA+5-HIAA absorbance change;
[0052] Fig.39 This is the light competition absorption diagram between DPA and 5-HIAA. DETAILED DESCRIPTION
[0053] Specific embodiment 1: This embodiment is a method for preparing a water-soluble, highly efficient, luminescent lanthanide complex having multiple hydrogen bonding sites, which is as follows:
[0054] 1. dissolving a rare earth salt in dimethylformamide to obtain a metal salt solution;
[0055] The rare earth salt is EuCl 3 6H 2 O、TbCl 3 6H 2 O, YbCl 3 6H 2 O、NdCl 3 6H 2 O or ErCl 3 6H 2 O;
[0056] 2. Dissolve 2,6-pyridinedicarboxylic acid in dimethylformamide to obtain 2,6-H 2 dpa solution;
[0057] 3. 2,6-H 2 The dpa solution is added to the metal salt solution to obtain a reaction system. The reaction system is heated to react under stirring conditions, and then the product is filtered under reduced pressure, washed and dried to obtain a dried solid. Water is added to the dried solid, and then it is treated with an ultrasonic two-dimensional material stripper until a transparent solution is formed. Finally, it is freeze-dried to obtain a water-soluble, high-efficiency luminescent lanthanide complex with multiple hydrogen bonding sites.
[0058] This specific embodiment uses rare earth elements and ligand 2,6-pyridinedicarboxylic acid to design a water-soluble fluorescent sensor. Rare earth as a hard acid and ligand hard base show strong coordination in water, which can effectively resist the competition of water molecules, thereby maintaining its stable luminescence performance. This specific embodiment can quickly and effectively detect the concentration of 5-HIAA in the urine of normal people and carcinoid patients.
[0059] The beneficial effects of this embodiment are:
[0060] This embodiment successfully designed a water-soluble lanthanide complex with rare earth salt as EuCl 3 6H 2 Taking Eu-DPA as an example, the prepared water-soluble and highly luminescent lanthanide complex Eu-DPA with multiple hydrogen bonding sites has a solubility of 14.03g / 100g in water and highly luminescent in water (the quantum efficiency reaches 93.08% in 1g / L aqueous solution, and the lifetime is 2.062ms). It is used as a fluorescent probe to achieve ultra-sensitive and highly selective fluorescence detection of the carcinoid marker 5-hydroxyindoleacetic acid (5-HIAA) in water, plasma and urine. The water solubility of Eu-DPA is due to the hydrogen bonds formed between water molecules, which has been confirmed by theoretical calculations. Eu-DPA shows obvious fluorescence quenching phenomenon for 5-HIAA, and the shift of FTIR absorption peak and 1 The results of HNMR titration all proved that intermolecular hydrogen bonds were formed between Eu-DPA and 5-HIAA. In addition, the results of DLS dynamic light scattering showed that hydrogen bonds enhanced the assembly effect between Eu-DPA and 5-HIAA. The unsaturated pyridine carboxylic acid oxygen in Eu-DPA formed electrostatic interactions with the hydroxyl and amino groups in 5-HIAA through intermolecular hydrogen bonds. These hydrogen bonds acted as "bridges" to form a charge transfer channel between Eu-DPA and 5-HIAA. Theoretical calculations further confirmed that multiple intermolecular hydrogen bonds can be formed, resulting in a synergistic effect. Using TAS and TRES techniques, the energy transfer path was analyzed, and it was verified that the fluorescence quenching mechanism was mainly that 5-HIAA blocked the energy transfer from the ligand to the rare earth. In addition, other water-soluble lanthanide complexes that emit light in the visible and near-infrared regions were synthesized. These complexes can be completely dissolved in water while maintaining good luminescence intensity. In order to better realize the application of actual in vivo detection, 5-HIAA was tested in urine samples, and good detection effects were obtained, with a detection limit of 1.46μM. In actual sample testing, the sensor can clearly distinguish between healthy people and sick people. The water-soluble lanthanide complexes developed in this embodiment and the linkage of their multiple hydrogen bonds provide a new approach for the development of lanthanide complex fluorescent materials in the field of biological detection, and also provide important scientific support for future in vivo detection and cancer marker analysis, which is of great significance for applications in the fields of biomedicine and clinical diagnosis.
[0061] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the concentration of the metal salt solution in step 1 is 0.06 mol / L to 0.07 mol / L. Other aspects are the same as those of specific embodiment 1.
[0062] Specific implementation method three: This implementation method is different from either specific implementation method one or two in that: the 2,6-H 2 The concentration of the dpa solution is 0.1 mol / L to 0.3 mol / L. The rest is the same as the first or second specific implementation.
[0063] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the concentration of 2,6-pyridinedicarboxylic acid in the reaction system described in step 3 is 0.05 mol / L to 0.15 mol / L; the concentration of rare earth salt in the reaction system described in step 3 is 0.02 mol / L to 0.04 mol / L. Others are the same as specific embodiments 1 to 3.
[0064] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 3, the reaction system is heated for 1 h to 1.5 h under the conditions of a stirring speed of 2.5 r / s to 3.5 r / s and a reaction temperature of 140° C. to 160° C. The rest is the same as specific embodiments 1 to 4.
[0065] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: in step 3, the product is filtered under reduced pressure using a Buchner funnel, then washed with ethanol, and finally dried at a temperature of 70°C to 100°C for 8h to 10h. The rest is the same as specific embodiments 1 to 5.
[0066] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that the mass ratio of the dried solid to the volume ratio of water in step 3 is 1 g: (3-5) mL. The rest is the same as Specific embodiments 1 to 6.
[0067] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: in step three, an ultrasonic two-dimensional material stripper is used for 3 to 5 minutes at room temperature, a power of 650 W to 750 W, and a frequency of 30 KHz to 40 KHz until a transparent solution is formed. The rest is the same as specific embodiments one to seven.
[0068] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the freeze drying in step 3 is freeze drying for 10 to 12 hours under vacuum and a drying temperature of -20°C to -30°C. The rest is the same as specific embodiments 1 to 8.
[0069] Specific embodiment 10: This embodiment is an application of a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites, and another application of the same as a luminescent sensor for the carcinoid marker 5-HIAA.
[0070] The following examples are used to verify the beneficial effects of the present invention:
[0071] Embodiment 1:
[0072] A method for preparing a water-soluble, highly efficient, luminescent lanthanide complex having multiple hydrogen bonding sites is carried out according to the following steps:
[0073] 1. 0.0033 mol EuCl 3 6H 2 O was dissolved in 50 mL of dimethylformamide (DMF) to obtain a metal salt solution;
[0074] 2. Dissolve 0.0100 mol of 2,6-pyridinedicarboxylic acid in 50 mL of dimethylformamide to obtain 2,6-H 2 dpa solution;
[0075] 3. Add 50mL 2,6-H 2 The dpa solution was added to 50 mL of a metal salt solution to obtain a reaction system. The reaction system was heated to react for 1 h at a stirring speed of 3 r / s and a temperature of 150°C. The product was then filtered under reduced pressure using a Buchner funnel, then washed with ethanol, and finally dried for 10 h at a temperature of 80°C to obtain a dried solid. 100 mL of water was added to 20 g of the dried solid. The solid was then treated for 3 min using a Scientz-CHF-5B ultrasonic two-dimensional material stripper at room temperature, a power of 720 W, and a frequency of 40 kHz to form a transparent solution. The solid was then freeze-dried for 10 h under vacuum at a temperature of -25°C to obtain a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites, namely Eu-DPA.
[0076] The chemical formula of the water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites is [H 2 N(Me) 2 ] 3 [Eu(2,6-dpa) 3 ].
[0077] Embodiment 2: This embodiment is different from Embodiment 1 in that: the EuCl 3 6H 2 O were replaced by TbCl 3 6H 2 O, YbCl 3 6H 2 O、NdCl 3 6H 2 O and ErCl 3 6H 2O, step 3 respectively obtains Tb-DPA, Yb-DPA, Nd-DPA, and Er-DPA. The rest is the same as in embodiment 1.
[0078] Comparative Experiment 1: This comparative experiment is different from Example 1 in that: in step 3, water addition, ultrasonic two-dimensional material exfoliation and freeze drying are omitted; the dried solid obtained in step 3 is Eu-DPA-1. The rest is the same as Example 1.
[0079] Comparative Experiment 2: This comparative experiment differs from Example 1 in that: 2,6-pyridinedicarboxylic acid in step 2 is replaced by D-dibenzoyltartaric acid, 4,4'-biphenyldicarboxylic acid, dibenzoylmethane and 1,10-phenanthroline respectively; and Eu-DBTA, Eu-BPDC, Eu-DBM and Eu-PHEN are obtained in step 3 respectively. The rest is the same as Example 1.
[0080] Comparative Experiment 3: The difference between this comparative experiment and Example 1 is that the EuCl 3 6H 2 O replaced by GdCl 3 6H 2 O, and Gd-DPA is obtained in step 3. The rest is the same as in embodiment 1.
[0081] (I) Structure:
[0082] The main function of the Scientz-CHF-5B ultrasonic two-dimensional material stripper is to enhance its solubility in water by reducing the particle size. In this complex, 2,6-pyridinedicarboxylic acid (DPA) serves as a tridentate ligand, providing three electron donor sites, which are derived from sp 3 The hybrid nitrogen atom and the two oxygen atoms on the pyridine ring. The carboxyl oxygen atom of DPA is 3+ Ion coordination, and through deprotonation to form a conjugated structure, the ligand surface is negatively charged. The other oxygen atom of the carboxylate group is easy to combine with substances with higher electropositivity and active hydrogen sites, promoting the formation of intermolecular hydrogen bonds. This structure helps to expose hydrogen bond receptor sites and form a single hydrogen bond on the same plane, thereby avoiding steric hindrance ( Figure 1 Schematic diagram of the structure of Eu-DPA). This mononuclear structure is beneficial to the directionality and saturation of hydrogen bonds. Theoretical calculations also confirm that Eu-DPA can form intermolecular hydrogen bonds with water molecules ( Figure 2 is the distance between Eu-DPA and water to form intermolecular hydrogen bonds. In the figure, the green ball is Eu, the gray ball is C, the red ball is O, the white ball is H, and the blue ball is N). By comparing their morphologies, the morphology of the complex treated with ultrasound becomes smaller and more uniform ( Figure 3 (Figure 2A and 2B are microscope and SEM images of Eu-DPA and Eu-DPA-1). Therefore, Eu-DPA shows good solubility in water.
[0083] (ii) Water solubility:
[0084] The solubility of Eu-DPA prepared in Example 1 was measured by gravimetric method, and it was found that 14.03 g of Eu-DPA could be dissolved in every 100 g of water, indicating that it was a readily soluble substance.
[0085] The Eu-DPA prepared in Example 1 was added into distilled water to prepare a concentration of 1 g / L to 150 g / L to test the dissolution time; Figure 4 is the dissolution time of Eu-DPA aqueous solutions with different concentrations; as can be seen from the figure, the dissolution rate is slower when the solution is close to saturation, while it can be dissolved within one minute at other concentrations.
[0086] The laser (wavelength of 532nm, power of 30mw) was used to irradiate the Eu-DPA-1 aqueous solution (concentration of 1g / L) and the Eu-DPA aqueous solution (concentration of 1g / L); the experimental results showed that neither the Eu-DPA synthesized by ultrasound-assisted method nor the Eu-DPA-1 synthesized in comparative experiment 1 showed obvious Tyndall effect. The Tyndall phenomenon usually indicates that the sample is a colloid, while its absence indicates a solution or suspension state; based on this, it can be judged that the Eu-DPA aqueous solution is in a solution state, while the Eu-DPA-1 aqueous solution is in a suspension state.
[0087] The dynamic light scattering (DLS) particle size distribution of Eu-DPA-1 aqueous solution (concentration of 1g / L) and Eu-DPA aqueous solution (concentration of 1g / L) was tested; the results showed that the particle size of Eu-DPA was too small and exceeded the detection range of DLS, while the average particle size of Eu-DPA-1 was 522.1nm ( Figure 5 (Figure 2A) is the dynamic light scattering particle size distribution of Eu-DPA-1 aqueous solution. This is consistent with previous observations that Eu-DPA is highly soluble in water, while Eu-DPA-1 is suspended due to its large particle size.
[0088] Eu-DPA-1 aqueous solution (concentration 1 g / L) and Eu-DPA aqueous solution (concentration 1 g / L) after standing for 10 hours using laser irradiation (wavelength 532 nm, power 30 mw); Figure 6 This is a comparison diagram of the Tyndall effect of Eu-DPA-1 aqueous solution and Eu-DPA aqueous solution after standing for 10 hours, a is Eu-DPA, b is Eu-DPA-1; it can be seen from the figure that after 10 hours of standing, the Eu-DPA aqueous solution remains clear without any sediment at the bottom, while in the Eu-DPA-1 aqueous solution, obvious complex precipitation can be observed at the bottom of the container.
[0089] Under ultraviolet light (wavelength 365nm, power 30mw), irradiate Eu-DPA-1 aqueous solution (concentration 1g / L) and Eu-DPA aqueous solution (concentration 1g / L) before and after standing for 10 hours to test the change in their luminescence intensity; Figure 7 The figure is a comparison of the luminescence intensity of Eu-DPA-1 aqueous solution and Eu-DPA aqueous solution before and after standing for 10 hours under ultraviolet light. It can be seen from the figure that the luminescence intensity of Eu-DPA remains unchanged in the solution, while Eu-DPA-1 shows strong luminescence at the bottom and weak luminescence in the upper clear liquid.
[0090] Under ultraviolet light (wavelength 365nm, power 30mw), irradiate the Eu-DPA aqueous solution (concentration 1g / L) that has been standing for 3 months to test the change in its luminescence intensity; Figure 8 The stability comparison chart of Eu-DPA aqueous solution after standing for 3 months under ultraviolet light; the time dependence shows that the luminescence intensity of the aqueous solution has almost no decay within 3 months, showing excellent dispersibility and stability.
[0091] Fig. 9 1H NMR of Eu-DPA and Eu-DPA-1 in deuterated water; As can be seen from the figure, the spectrum before and after ultrasonic two-dimensional material exfoliation Figure 1 This proves that ultrasonic exfoliation of two-dimensional materials enhances their water solubility, but does not change their structure, further proving that their structure does not change in aqueous solution.
[0092] Fig.10 is the X-ray diffraction pattern of Eu-DPA; Fig.11 This is the infrared spectrum of Eu-DPA; as can be seen from the figure, the successful synthesis of Eu-DPA is confirmed.
[0093] The Eu-DPA aqueous solution prepared in Example 1 which had been left to stand for 3 months was freeze-dried again to form a powder; Fig.12 The XRD comparison diagram of Eu-DPA-1, Eu-DPA and Eu-DPA freeze-dried after standing in water for 3 months. As can be seen from the figure, the PXRD data of the powder before and after standing in water did not change. This shows that the structure of Eu-DPA is stable in a long-term aqueous solution environment.
[0094] The Eu-DPA prepared in Example 1 was heated at 30° C., 40° C., 50° C., 60° C. and 70° C. for 5 min respectively, and then a fluorescence test was performed to verify the temperature stability of Eu-DPA; Fig.13 This is a stability comparison chart of Eu-DPA after heating; the results show that the complex has good stability in the temperature range of 30℃~70℃.
[0095] The above results demonstrate the feasibility of Eu-DPA materials in practical applications. These research results reveal the excellent photophysical properties of Eu-DPA in water, showing excellent solubility and luminescence stability, thus confirming the practical application value of Eu-DPA in biosensing and luminescence detection.
[0096] The water solubility and excellent photophysical properties of Eu-DPA originate from its unique molecular structure, in which each Eu-DPA molecule adopts a distorted triangular prism arrangement. Studies have shown that the solvent quenching phenomenon of rare earth ions in aqueous solutions is mainly due to the interaction between the rare earth ions and the OH vibrations around the ligands. This is usually the result of solvent molecules entering the metal center and interacting with the metal center. Solvent water is a common quencher of known luminescent lanthanide complexes, and its OH bond vibrations interfere with the energy transfer from the ligand triplet energy level to the lanthanide ion. This distorted triangular prism structure helps to avoid the central Eu 3+ The ions are in direct contact with the solvent water molecules, while effectively shielding the solvent molecules from Eu 3+ Direct coordination of water molecules prevents luminescence quenching due to OH bond vibration in water, significantly reducing the possibility of non-radiative quenching. In addition, molecules of water-soluble substances usually contain polar groups or shorter carbon chains. Eu-DPA not only contains polar hydrophilic groups, but also can form intermolecular hydrogen bonds with water molecules, further suppressing the vibration effect of OH bonds. This allows Eu-DPA to dissolve in water without being negatively affected by solvent water, thereby maintaining good luminescence intensity. These characteristics make Eu-DPA a potential excellent luminescent material in aqueous environments, suitable for use in biomarkers and other related applications.
[0097] Under fluorescence, the Eu-DPA aqueous solution (concentration of 1 g / L) was irradiated to test its absorption spectrum, excitation spectrum and emission spectrum; Fig.14 Figure 1 shows the absorption spectrum, excitation spectrum and emission spectrum of a 1g / L Eu-DPA aqueous solution under fluorescence illumination. a is the emission spectrum, b is the absorption spectrum, and c is the excitation spectrum. As can be seen from the figure, when the concentration of Eu-DPA in the aqueous medium is 1g / L, its absorption spectrum, excitation spectrum and emission spectrum all show significant characteristics. The broad absorption band from 200nm to about 350nm is attributed to the ligand DPA, indicating energy transfer from the singlet or triplet excited state of the ligand to the metal. Under 287nm light excitation, Eu-DPA shows a strong red color visible to the naked eye, and its emission spectrum is mainly composed of Eu 3+ 594, 613, 655 and 692nm 5 D 0 - 7 F j Transition composition.
[0098] The quantum yield and lifetime data of the Eu-DPA aqueous solution (concentration of 1 g / L) prepared in Example 1 were measured at room temperature and 612 nm wavelength. Fig.15 is the quantum efficiency diagram of Eu-DPA aqueous solution; Fig.16 This is the fluorescence lifetime diagram of Eu-DPA aqueous solution; as can be seen from the figure, the quantum efficiency of Eu-DPA reaches 93.08%, the lifetime is 2.062ms, and the lifetime hardly changes after being converted into a soluble complex.
[0099] The Eu-DPA and its aqueous solution prepared in Example 1, the Eu-DPA-1 and its aqueous solution prepared in Comparative Experiment 1, and the Eu complex aqueous solution prepared in Comparative Experiment 2 were irradiated under sunlight and ultraviolet light (wavelength of 365 nm, power of 30 mw), respectively, and then the Eu-DPA aqueous solution, the Eu-DPA-1 aqueous solution, and the Eu complex aqueous solution prepared in Comparative Experiment 2 were filtered using a dialysis bag (3500D), and then irradiated with sunlight and ultraviolet light again;
[0100] Fig.17 Comparison of Eu-DPA and Eu-DPA-1 under sunlight and ultraviolet irradiation, a) Eu-DPA and its aqueous solution (concentration of 1g / L), Eu-DPA-1 and its aqueous solution (concentration of 1g / L), b) Eu-DPA aqueous solution of different concentrations (concentration 0.1g / L to 3g / L), c) Comparison of the luminescence of Eu-DPA-1 aqueous solution (concentration of 1g / L) and Eu-DPA aqueous solution (concentration of 1g / L) before and after dialysis bag filtration under ultraviolet light (wavelength of 365nm, power of 30mw) (the dotted box is a photo of the real sample), d) Comparison of the photos of Eu complex aqueous solution (concentration of 1g / L) under sunlight and ultraviolet light before and after dialysis bag filtration. As can be seen from the figure, the Eu-DPA can emit strong red light under ultraviolet light, whether in solid state or dissolved in water, and appears as a transparent solution under sunlight, while Eu-DPA-1 appears white and turbid ( Fig.17 a). Eu-DPA aqueous solutions of different concentrations all appear as transparent solutions and emit bright red light ( Fig.17 b). The large-sized particles in the Eu-DPA aqueous solution and the Eu-DPA-1 aqueous solution were filtered by dialysis using a semipermeable membrane. The aqueous solution of Example Eu-DPA still glowed after filtration, which proved that the particle size was reduced due to ultrasound assistance, that is, Eu-DPA appeared clear in the aqueous solution at room temperature, and the luminescence intensity did not change; while most of the solid matter of Eu-DPA-1 remained in the semipermeable membrane due to its large particle size, and only a small amount of small-sized particles passed through the semipermeable membrane. After filtration, the luminescent particles were filtered out, and Eu-DPA-1 lost its luminescence ( Fig.17c). The fluorescence spectrum shows that the luminescence intensity of Eu-DPA is nearly twice that of Eu-DPA-1, which further proves the advantage of ultrasound-assisted method in preparing high-performance water-soluble luminescent materials. The Eu complexes prepared in comparative experiment 2 were further compared. These complexes all showed a suspended state that was insoluble in water and lost luminescence after filtration in the dialysis bag ( Fig.17 d). These results indicate that the excellent solubility and luminescent properties of Eu-DPA in water give it a significant potential in biolabeling and other related applications.
[0101] In order to verify the universality of water solubility, Example 2 further synthesized the same series of soluble rare earth complexes, and selected the visible light luminescent rare earth Tb and the commonly used near-infrared luminescent rare earths Yb, Nd and Er. 2,6-pyridinedicarboxylic acid (DPA) was used as a ligand, and the same ultrasound-assisted synthesis method was adopted to study their luminescence properties. According to the general design strategy, Tb-DPA, Yb-DPA, Nd-DPA, and Er-DPA are all expected to have good water solubility and luminescence properties. The experimental results are consistent with expectations. The rare earth complex solution synthesized by the ultrasound-assisted method appears clear and transparent, and the luminescence intensity remains stable ( Fig.18 The Tb-DPA, Yb-DPA, Nd-DPA, Er-DPA and their aqueous solutions prepared in Example 2 are shown in Figure 1). This not only proves that the solubility strategy is effective, but also shows its universality. The successful implementation of this strategy shows that the water solubility of the complex is mainly due to the hydrogen bonds formed between water molecules and the polar side groups in the ligands, which has been verified in different rare earth complexes. These results provide a solid foundation for the future development of more types of water-soluble rare earth complexes.
[0102] (III) Testing:
[0103] Testing the performance of the luminescent sensor with Eu-DPA as the carcinoid marker 5-HIAA:
[0104] Fig.19 Schematic diagram of the process of detecting 5-HIAA by Eu-DPA;
[0105] Eu-DPA and 5-HIAA were dissolved in water respectively, wherein the concentration of Eu-DPA aqueous solution was 1 g / L; when mixing, 1 mL of Eu-DPA aqueous solution and 1 mL of 5-HIAA aqueous solution were added respectively, so that the concentration of 5-HIAA in water was 10 -3mol / L; at the same time, the word "5-HIAA" was written on black cardboard using Eu-DPA aqueous solution, and then 5-HIAA aqueous solution was applied to this area; and its emission spectrum was tested using an excitation wavelength of 287nm, with the slit set to 2.5μm, the excitation filter to 290nm, the emission filter to 450nm, and the scanning speed to 1200cm / s. Fig. 20 The detection ability of Eu-DPA for 5-HIAA, a is the detection picture, and b is the actual picture. The study found that after adding 5-HIAA, the luminescence intensity of Eu-DPA at 613nm decreased rapidly, and it was observed that the sample began to emit bright red light in the area with the words "5-HIAA"; and after testing, as the concentration of 5-HIAA increased, the luminescence became dim, indicating that Eu 3+ The luminous intensity of the components rapidly decreased. Subsequently, the CIE chromaticity analysis of the samples was performed. Fig.21 The CIE chromaticity analysis diagram of Eu-DPA with the addition of 5-HIAA; the results show that with the gradual addition of 5-HIAA, the CIE color changes from red to blue, showing a red to blue luminescence color change process. This color change is due to the formation of multiple hydrogen bonds between 5-HIAA and DPA, which shortens the distance between molecules, thereby accelerating energy transfer and electron transfer, resulting in rapid luminescence quenching reaction. In order to further verify the sensitivity of Eu-DPA as a 5-HIAA luminescence sensor.
[0106] The Eu-DPA and 5-HIAA prepared in Example 1 were dissolved in water respectively to obtain Eu-DPA aqueous solution and 5-HIAA aqueous solution, wherein the concentration of the Eu-DPA aqueous solution was 1 g / L. During mixing, 1 mL of the Eu-DPA aqueous solution and the 5-HIAA aqueous solution were added respectively, so that the concentration of 5-HIAA in the mixed solution was 0 μM to 22 μM; and the emission spectrum was tested using an excitation wavelength of 287 nm, wherein the slit was set to 2.5 μm, the excitation filter was 290 nm, the emission filter was 450 nm, and the scanning speed was 1200 cm / s. Fig. 22 5-HIAA in H at room temperature 2 O quenching effect on Eu-DPA, a is the concentration dependence curve, b is the Ksv curve; it can be clearly seen from the figure that with the increase of the concentration of 5-HIAA aqueous solution, the luminescence intensity of Eu-DPA gradually decreases. The Stern-Volmer curve of Eu-DPA shows that there is a good linear relationship between concentration and relative luminescence intensity (R 2 =0.992), and the KSV value reached 1.1021 μM -1 In addition, the standard deviation of the luminescence intensity of the blank sample was 0.04785 by measuring it at least five times, and the lower limit of detection (LOD) was calculated to be 1.37×10 -7These results demonstrate that Eu-DPA has extremely high sensitivity and practicality in biosensing and luminescence detection, and is expected to play an important role in clinical and biomarker analysis.
[0107] In order to evaluate the performance of Eu-DPA in practical applications, Eu-DPA and 5-HIAA prepared in Example 1 were dissolved in simulated urine (concentration of 10 -3 mol / L urea solution) or serum sample (PBS buffer containing bovine serum, bovine serum concentration is 1g / L), wherein the concentration of Eu-DPA in Eu-DPA urine and Eu-DPA serum samples is 1g / L, and when mixed, 1mL of Eu-DPA urine and 5-HIAA urine are added respectively, so that the concentration of 5-HIAA in urine is 0μM to 60μM; or 1mL of Eu-DPA serum sample and 5-HIAA serum sample are added respectively, so that the concentration of 5-HIAA in serum is 0μM to 34μM. The emission spectrum is tested using an excitation wavelength of 287nm, wherein the slit is set to 2.5μm, the excitation filter is 290nm, the emission filter is 450nm, and the scanning speed is 1200cm / s. Fig.23 The quenching effect of 5-HIAA on Eu-DPA in urine at room temperature, a is the concentration dependence curve, b is the Ksv curve; the decreasing trend of the luminescence intensity is similar to the detection result of 5-HIAA in aqueous solution, and the Stern-Volmer curve shows an excellent linear relationship (R 2 =0.994), and the calculated limit of detection (LOD) was 1.46 μM. Fig.24 Figure 1 is the quenching effect of 5-HIAA on Eu-DPA in serum at room temperature, a is the concentration dependence curve, and b is the Ksv curve. As can be seen from the figure, Eu-DPA exhibits a good detection effect in serum, and the Stern-Volmer curve shows an excellent linear relationship (R 2 =0.994), and the detection limit (LOD) was calculated to be 2.23 μM.
[0108] To further verify the ability of different rare earth complexes (Ln-DPA) to detect 5-HIAA, the near-infrared luminescent complexes Yb-DPA, Nd-DPA and Er-DPA prepared in Example 2 were used for experiments. Yb-DPA, Nd-DPA, Er-DPA and 5-HIAA were dissolved in water, respectively, and the concentration of the Ln-DPA aqueous solution was 1 g / L. When mixing, 1 mL of each of the Ln-DPA aqueous solution and the 5-HIAA aqueous solution was added to make the concentration of 5-HIAA in the water 10. -3mol / L. The emission spectrum of Yb-DPA was tested using an excitation wavelength of 342 nm, the emission spectrum of Nd-DPA was tested using an excitation wavelength of 356 nm, and the emission spectrum of Er-DPA was tested using an excitation wavelength of 332 nm. Fig.25 Schematic diagram of biological detection of carcinoid markers using different rare earth complexes (Ln-DPA). Fig.26 The changes in the fluorescence intensity of 5-HIAA detected by different rare earth complexes prepared in Example 2 (Ln-DPA), f) Yb-DPA, j) Nd-DPA, h) Er-DPA. It was observed experimentally that these complexes all showed good responses when detecting 5-HIAA. These results show that the synthesized materials are not limited to Eu-DPA, and other rare earth elements such as erbium, neodymium and erbium DPA complexes also have the potential to be used as practical sensors. It reflects the wide application possibility of Ln-DPA complexes in biological detection, especially the fluorescence emission in the near-infrared region can provide additional advantages for clinical applications.
[0109] In view of the complexity of biological samples, selectivity and competition experiments were conducted to evaluate the potential of Eu-DPA prepared in Example 1 for sensing 5-HIAA. Other coexisting species present in urine and serum were tested, including histidine, aspartic acid, proline, tyrosine, glutamic acid, glucose, urea, various salts, etc. Water was used as the solvent for the next step of preparation. The histidine concentration in the anti-interference test was 10 -3 mol / L, aspartic acid concentration is 10 -3 mol / L, proline concentration is 10 -3 mol / L, tyrosine concentration is 10 -3 mol / L, glutamate concentration is 10 -3 mol / L, glucose concentration is 10 -3 mol / L, urea concentration is 10 - 3 mol / L, various salt concentrations are 10 -3 mol / L, 5-HIAA concentration is 10 -3 mol / L, Eu-DPA concentration was 1 g / L; and the emission spectrum was tested using an excitation wavelength of 287 nm, with the slit set to 2.5 μm, the excitation filter to 290 nm, the emission filter to 450 nm, and the scanning speed to 1200 cm / s. Fig. 27For anti-interference tests and real urine detection, a) normal and pathological ranges corresponding to different 5-HIAA concentrations in real urine detection, b) detection of each substance, c) the ability of Eu-DPA to detect 5-HIAA in the presence of interferents, d) real urine detection of normal people and carcinoid patients. The results showed that only 5-HIAA caused significant fluorescence quenching at 612nm, while other substances had no significant effect on the emission intensity. Even in the presence of interferents in human serum or urine, the quenching effect did not change significantly, and Eu-DPA was able to maintain good detection ability for 5-HIAA. It shows that the Eu-DPA sensor shows excellent selectivity and excellent anti-interference ability when monitoring 5-HIAA. Therefore, Eu-DPA can be used as a highly selective biosensor for quantitative detection of 5-HIAA in urine. Evaluate the specific performance of Eu-DPA in detecting 5-HIAA in urine samples. After adding different concentrations of 5-HIAA to the prepared urea solution, the concentration of 5-HIAA is normal in the range of 1.8 to 6.0 mg / 24h (corresponding to a relative intensity of 1.19-1.51); more than 25 mg / 24h may indicate carcinoid (corresponding to a relative intensity greater than 1.96), while more than 50 mg / 24h can be diagnosed as carcinoid (corresponding to a relative intensity greater than 2.58). Mild elevations of 5-HIAA in urine can be seen in other gastrointestinal diseases (corresponding to a relative intensity between 1.51-1.96), while low levels may occur in patients with kidney disease (corresponding to a relative intensity less than 1.91) ( Fig. 27 a). Fig. 27 As shown in Figure d, the test results of adding healthy human urine are in the normal range, while the urine of carcinoid patients shows a high value of relative intensity greater than 2.58, thus clearly distinguishing between healthy and diseased people. These results demonstrate the feasibility and accuracy of the Eu-DPA sensor for detecting 5-HIAA in real urine samples.
[0110] (IV) Mechanism:
[0111] 1. Hydrogen Bond:
[0112] In view of the above-mentioned fluorescence quenching phenomenon, the mechanism of fluorescence quenching between Eu-DPA and 5-HIAA was further explored, especially from the perspective of hydrogen bonding. Fig.28Schematic diagram of hydrogen bond interaction between Eu-DPA and 5-HIAA; Eu-DPA acts as a hydrogen bond acceptor, with six hydrogen bond acceptor sites per molecule, while 5-HIAA has three hydrogen bond donor sites. During the reaction, one 5-HIAA molecule can bind to one or more Eu-DPA molecules through hydrogen bonds, thereby generating a linkage effect. As shown in the figure, 5-HIAA acts as a hydrogen bond donor, and its NH and OH groups can form intermolecular hydrogen bonds with the acceptor sites in Eu-DPA. These multi-site hydrogen bond formations enhance the interaction between molecules, resulting in more efficient energy transfer, accelerating the electron transfer process, and promoting fluorescence quenching. The addition of 5-HIAA significantly changes the electronic structure and photophysical behavior of Eu-DPA, which explains why an increase in the concentration of 5-HIAA leads to a significant decrease in luminescence intensity.
[0113] A variety of analytical techniques were used to explore the interaction between 5-HIAA and Eu-DPA prepared in Example 1, especially from the perspective of electrostatic interaction and hydrogen bond formation. Eu-DPA and 5-HIAA were dissolved in water to obtain Eu-DPA aqueous solution and 5-HIAA aqueous solution, wherein the concentration of Eu-DPA aqueous solution was 1 g / L. When mixing, 1 mL of each of Eu-DPA aqueous solution and 5-HIAA aqueous solution was added to make the concentration of 5-HIAA in water 10 -3 mol / L; Fig.29 This is a point comparison diagram of Eu-DPA and Eu-DPA+5-HIAA; through ζ potential analysis, it was found that the initial ζ potential of Eu-DPA was -17.5mV, indicating that its surface was negatively charged. After adding 1mL 5-HIAA, the ζ potential became -1.5mV, showing that the positively charged 5-HIAA interacted with Eu-DPA through electrostatic interaction, resulting in a significant change in the ζ potential.
[0114] The Eu-DPA and 5-HIAA prepared in Example 1 were dissolved in water to obtain Eu-DPA aqueous solution and 5-HIAA aqueous solution, wherein the concentration of the Eu-DPA aqueous solution was 1 g / L, and the concentration of the 5-HIAA aqueous solution was 10 -3 mol / L, the Eu-DPA aqueous solution was mixed with the 5-HIAA aqueous solution; Fig.30 The hydrogen bonding in the system is demonstrated in Figure 2. b) The gradual addition of 5-HIAA to Eu-DPA 1H NMR diagram, (1) is 8 mg Eu-DPA + 2 mg 5-HIAA, (2) is 8 mg Eu-DPA + 4 mg 5-HIAA, (3) is 8 mg Eu-DPA + 6 mg 5-HIAA, (4) is 8 mg Eu-DPA + 8 mg 5-HIAA, (5) is 8 mg Eu-DPA + 10 mg 5-HIAA, c) FT-IR spectrum of dynamic light scattering particle size distribution of Eu-DPA + 5-HIAA, d) DLS test of 5-HIAA and 1 mg Eu-DPA + 1 mg 5-HIAA. 1 The results of HNMR titration showed that as the content of 5-HIAA increased, the chemical shift of proton H1, moved to the low field. This change in peak position indicated that the hydroxyl and amino groups of 5-HIAA participated in the formation of intermolecular hydrogen bonds with Eu-DPA ( Fig.30 b) In addition, FTIR analysis provides additional evidence for hydrogen bonding. When 5-HIAA is gradually added to Eu-DPA, the 3300-3500 cm -1 The absorption peak in this region shows an obvious shift to low frequency, which is a typical characteristic of the formation of intermolecular hydrogen bonds. -1 The NH bond peak disappears, indicating that the NH bond participates in the formation of hydrogen bonds ( Fig.30 c). DLS analysis showed that the Eu-DPA(5-HIAA) complex formed larger aggregates with an average size of 490.5 d.nm in aqueous solution ( Fig.30 d), which also confirms the enhanced intermolecular assembly due to hydrogen bond formation.
[0115] Fig.31 The XPS graphs of 5-HIAAEu-DPA, 5-HIAA and Eu-DPA+5-HIAA, e) O 1s spectrum; f) N 1s spectrum; g) Eu 4d spectrum. In the figure, Before(Eu-DPA) represents Eu-DPA, Before(5-HIAA) represents 5-HIAA, and After is Eu-DPA+5-HIAA; XPS analysis further confirmed the specific site of hydrogen bond formation. The binding energy of the C=O bond in the O 1s spectrum changed from 531.82eV to 532.03eV, indicating that a new bond connection was formed on the C=O bond, which is consistent with the formation of a hydrogen bond between NH and OH of 5-HIAA. The decrease in the binding energy of the NH bond in the N 1s spectrum also supports the formation of a hydrogen bond.
[0116] Fig.32Theoretical calculation diagram, h) Electrostatic potential of Eu-DPA and 5-HIAA, i) Hydrogen bond distance between DPA and 5-HIAA, j) Change of dihedral angle of Eu-DPA after adding 5-HIAA. Density functional theory (DFT) method was used to calculate the hydrogen bond interaction between 5-HIAA and Eu-DPA. Electrostatic potential diagram ( Fig.32 h) shows that there are strong hydrogen bond interactions between the amine and hydroxyl groups on the 5-HIAA molecule and Eu-DPA. The distances and binding energies of these hydrogen bonds are and -2.79eV, see Fig.32 i. In addition, the structural changes within the Eu-DPA molecule, especially the rotation of the pyridine ring, were analyzed. Fig.32 As shown in Figure j, the dihedral angle Δθ of the Eu-DPA molecule not bound to 5-HIAA is 102.71°. When 5-HIAA is added, the dihedral angle decreases to Δθ = 99.64°. This change in the dihedral angle clearly shows that the formation of hydrogen bonds limits the rotational freedom of the pyridine ring in Eu-DPA, which may increase the non-radiative attenuation path during photoexcitation. This phenomenon can explain why the fluorescence intensity of Eu-DPA is quenched in the presence of 5-HIAA. Restricting the rotation of the pyridine ring not only reduces the structural relaxation ability of the molecule, but also may promote the dissipation of energy through non-radiative paths, thereby reducing the luminescence efficiency of Eu-DPA. These findings reflect the key role of hydrogen bonds in regulating photophysical processes.
[0117] The effect of pH on the fluorescence intensity of the Eu-DPA (5-HIAA) system was investigated. Eu-DPA and 5-HIAA were dissolved in water to obtain Eu-DPA aqueous solution and 5-HIAA aqueous solution, respectively. The concentration of the Eu-DPA aqueous solution was 1 g / L. When mixing, 1 mL of each of the Eu-DPA aqueous solution and the 5-HIAA aqueous solution was added to make the concentration of 5-HIAA in the water 10. -3 mol / L; and the emission spectrum was tested using an excitation wavelength of 287nm, with the slit set to 2.5μm, the excitation filter set to 290nm, the emission filter set to 450nm, and the scanning speed set to 1200cm / s. The detection ability of Eu-DPA for 5-HIAA was tested under neutral (pH 7.4), acidic (pH 3), and alkaline (pH 9) conditions; Fig.33Figure 2 is the detection ability diagram of Eu-DPA for 5-HIAA under neutral, acidic and alkaline conditions, a is Eu-DPA aqueous solution, b is neutral environment, c is acidic environment, and d is alkaline environment; it can be seen from the figure that Eu-DPA exhibits strong luminescence in aqueous solution without the addition of 5-HIAA (pink line). In a neutral environment (pH 7.4), the luminescence intensity of 5-HIAA for Eu-DPA is the lowest, indicating that under neutral conditions (blue line), the luminescence burst effect of 5-HIAA on Eu-DPA is the strongest. In an acidic environment, the carboxylic acid group of Eu-DPA may be partially protonated, thereby reducing the electrostatic interaction and hydrogen bond formation with 5-HIAA (green line Eu-DPA-a). However, under alkaline conditions (pH 9), the amino and hydroxyl groups of 5-HIAA may be partially deprotonated, further weakening the electrostatic interaction and hydrogen bond with Eu-DPA (orange line Eu-DPA-b). The role of hydrogen bonds in luminescence bursts is further verified. Experiments show that Eu-DPA exhibits strong fluorescence in aqueous solution without the addition of 5-HIAA. After the addition of 5-HIAA, the amino and hydroxyl groups on its surface form a Eu-DPA (5-HIAA) complex with the carboxylic acid groups in Eu-DPA through electrostatic interactions and hydrogen bonding, resulting in charge transfer and quenching of Eu-DPA fluorescence. It was found that the fluorescence intensity was lowest in a neutral environment (pH 7.4), indicating that 5-HIAA has the strongest fluorescence quenching effect on Eu-DPA under neutral conditions. In an acidic environment, the carboxylic acid groups of Eu-DPA may be partially protonated, thereby reducing the electrostatic interaction and hydrogen bond formation with 5-HIAA. Under alkaline conditions, the amino and hydroxyl groups of 5-HIAA may be partially deprotonated, further weakening the electrostatic interaction and hydrogen bonding with Eu-DPA.
[0118] In order to further verify the role of hydrogen bonds in fluorescence quenching, the functional group in 5-HIAA that can serve as a hydrogen bond donor was replaced with benzocyclopentadiene (indene) which does not have the property of a hydrogen bond donor. The luminescence of Eu-DPA and indene was observed under the same test conditions: Eu-DPA and benzocyclopentadiene were dissolved in water respectively to obtain Eu-DPA aqueous solution and benzocyclopentadiene aqueous solution, wherein the concentration of Eu-DPA aqueous solution was 1 g / L. When mixing, 1 mL of each of Eu-DPA aqueous solution and benzocyclopentadiene aqueous solution was added to make the concentration of benzocyclopentadiene in water 10 -3 mol / L; and the emission spectrum was tested using an excitation wavelength of 287 nm, with the slit set to 2.5 μm, the excitation filter to 290 nm, the emission filter to 450 nm, and the scanning speed to 1200 cm / s. Fig.34 This is the quenching effect diagram of Eu-DPA and Eu-DPA+indene; the results show that the fluorescence intensity is almost unchanged.
[0119] These results clearly indicate that the intermolecular hydrogen bond formation between 5-HIAA and Eu-DPA has a significant effect on the fluorescence of Eu-DPA, and this effect shows different intensities at different pH values, further verifying the key role of intermolecular hydrogen bonds in stabilizing the structure and regulating the fluorescence properties. This discovery is of great significance for the design and optimization of Eu-DPA-based biosensors.
[0120] 2. The quenching stage involves two processes:
[0121] The fluorescence quenching stage involves two main processes: the first process involves the formation of electrostatic interactions between the unsaturated pyridine carboxylic acid oxygen in Eu-DPA and the hydroxyl and amino groups in 5-HIAA through intermolecular hydrogen bonds. These hydrogen bonds act as "bridges" to form a charge transfer channel between Eu-DPA and 5-HIAA. The second process is the dynamic quenching caused by the excited state collision between 5-HIAA and the Eu-DPA fluorescent probe, which leads to fluorescence quenching accompanied by electron transfer. Eu-DPA and 5-HIAA were dissolved in water respectively, where the concentration of the Eu-DPA aqueous solution was 1g / L; when mixing, 1mL of the Eu-DPA aqueous solution and the 5-HIAA aqueous solution were added each, so that the concentration of 5-HIAA in the water was 10 -3 mol / L, and then the emission spectrum was tested using an excitation wavelength of 287 nm, with the slit set to 2.5 μm, the excitation filter to 290 nm, the emission filter to 450 nm, and the scanning speed to 1200 cm / s; Fig.35 It is the fluorescence intensity diagram of Eu-DPA and Eu-DPA+5-HIAA; Fig.36 Figure 2 is the fluorescence lifetime diagram of Eu-DPA and Eu-DPA+5-HIAA; by observing the fluorescence changes of Eu-DPA after adding a certain concentration of 5-HIAA, it can be clearly seen that the intensity of the rare earth peak Eu at 612nm decreases, and the corresponding fluorescence lifetime also shows a change from 2.06ms to 1.87ms. In addition, it was observed that after adding 5-HIAA, the emission peak of the DPA ligand at 450nm increased significantly, and it was speculated that energy transfer may have occurred between Eu-DPA and 5-HIAA. However, the energy transfer process from ligand to metal and its effect on the addition of 5-HIAA cannot be directly observed only through the changes in fluorescence intensity and lifetime, which limits the accurate determination of the sensitization mechanism and transfer path. Therefore, time-resolved fluorescence spectroscopy is used to further characterize this process to determine the electron transfer path.
[0122] 3. Ligand transfer to Eu and changes after 5-HIAA addition:
[0123] The luminescence dynamics and time-resolved fluorescence spectroscopy (TRES) on the nanosecond time scale were tested using pulsed excitation at 287 nm. 3+ Gd 3+ Analogue (Gd-DPA prepared in comparative experiment 3), which is based on Gd 3+ The cation lacks the energy to excite the 4f* state, so no reaction to Gd occurs. 3+ energy transfer; Fig.37 It is the structural diagram of Gd-DPA and Eu-DPA. It can be seen from the figure that the structure of Gd-DPA and Eu-DPA is the same, so the TRES of Gd-DPA can be compared with Eu-DPA.
[0124] Eu-DPA and 5-HIAA were dissolved in water respectively, wherein the concentration of Eu-DPA aqueous solution was 1 g / L; when mixing, 1 mL of Eu-DPA aqueous solution and 1 mL of 5-HIAA aqueous solution were added respectively, so that the concentration of 5-HIAA in water was 10 -3 mol / L; Fig.38 Mechanism analysis diagram, a) Time-resolved fluorescence spectrum of Gd-DPA, b) Time-resolved fluorescence spectrum of Eu-DPA, c) Time-resolved fluorescence spectrum of Eu-DPA+5-HIAA, d) HOMO and LUMO of Eu-DPA and Eu-DPA+5-HIAA, e) Eu-DPA femtosecond TA contour map, f) Eu-DPA+5-HIAA femtosecond TA contour map, g) ΔEu-DPA absorbance change; h) ΔEu-DPA+5-HIAA absorbance change. By comparing the time-resolved spectra of Gd-DPA and Eu-DPA, it was observed that Gd-DPA showed a broad spectrum at 400nm ( Fig.38 a), which reflects the ligand S 1 →S 0 The fluorescence emission of Eu-DPA is mainly concentrated here. In the Eu-DPA sample, the ligand fluorescence at 400nm almost disappears, indicating that all the luminescence is transferred to Eu, especially Eu 3+ Ions at 612nm 5 D 0 → 7 F 2 The transition emission is very clear, and its intensity changes over time, showing a strong luminescence at 612nm. This result confirms the rapid electron transfer from the ligand DPA to the rare earth Eu ( Fig.38b). To further analyze the evolution of the excited state, the time-resolved spectrum of Eu-DPA after adding 5-HIAA was measured. After adding 5-HIAA, it was observed that the luminescence intensity of Eu was significantly weakened, showing a thin line, indicating that in this case the excitation of rare earth Eu is not affected by the ligand DPA, but shows independent luminescence behavior, and the fluorescence of the ligand is still displayed in a wide spectral range of 360nm ( Fig.38 c). The blue shift of the spectrum may be the result of the combined effects of factors such as changes in the charge distribution within the fluorescent molecules, the influence of the chemical environment, the molecular arrangement, and the solvent effect.
[0125] Further density functional theory (DFT) calculations were performed to analyze the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of Eu-DPA and Eu-DPA+5-HIAA complexes. In the Eu-DPA and Eu-DPA+5-HIAA complexes, the electrons at the HOMO energy level are mainly confined near the metal. During the excitation process, the electrons of Eu-DPA usually transition from HOMO to LUMO, indicating that the electrons are transferred to the ligand; in the case of Eu-DPA+5-HIAA, the electrons are transferred to 5-HIAA, resulting in a change in the internal charge distribution. In addition, after the addition of 5-HIAA, the energy level difference between HOMO and LUMO dropped from 0.089 to 0.05, indicating that the smaller the energy reduction from free electrons to molecular bonding, the easier it is for electrons to transition from HOMO to LUMO, making the molecule more unstable and increasing the possibility of chemical changes ( Fig.38 d). This change indicates that the addition of 5-HIAA not only hinders the electron transfer from the ligand DPA to the rare earth Eu, but also promotes the transfer of electrons to 5-HIAA, further leading to fluorescence quenching. ( Fig.39 (Figure 5A) shows that there is an obvious overlap between the absorption spectra of the ligand DPA and 5-HIAA, which indicates that the energy may be competitively absorbed by 5-HIAA, thereby reducing the energy transfer efficiency of Eu3+ ions and significantly leading to fluorescence quenching.
[0126] These results clearly demonstrate the main energy transfer pathway. The energy transfer process begins with light absorption by the ligand, followed by intersystem crossing (ISC) from S1 to T1, followed by energy transfer from T1 to the rare earth element Eu, and finally luminescence at the metal center. However, when the analyte 5-HIAA is added, it blocks the energy transfer pathway from the ligand to the rare earth, resulting in fluorescence quenching.
[0127] The entire energy transfer process was further studied on a shorter time scale. Femtosecond transient absorption (fs-TA) measurements were performed under 287nm excitation to gain insight into the photoexcited charge transfer and recombination dynamics after the addition of the analyte 5-HIAA. The excited state dynamics of the ligand DPA and the rare earth Eu after UV excitation were analyzed using a photodetection pulse. Due to the return to the ground state caused by stimulated radiation or spontaneous radiation, the sample will produce fluorescence in this process, which in turn leads to an increase in the light intensity received by the detector, resulting in a negative ΔA signal. Fig.38 e, the ligand stimulated emission (SE) can be observed at 400 nm, while Fig.38 g shows four stimulated emission peaks at 594, 618, 650, and 699 nm, which are attributed to Eu 3+ Ions from 5 D 0 Excited state 7 F J (J = 0-4) energy level transition. On the fs time scale, it can be observed that the fluorescence of the Eu-DPA ligand gradually decays, while at the same time the fluorescence of Eu increases with time delay. These spectral features further confirm that in the Eu-DPA complex, energy is rapidly transferred from the ligand DPA to the rare earth Eu, supporting the hypothesis of energy transfer. It further confirms the rapid transfer of electrons from the ligand DPA to the rare earth Eu in the complex Eu-DPA.
[0128] The kinetic behavior of the Eu-DPA complex after the addition of 5-HIAA was further studied. Femtosecond transient absorption (fs-TA) measurements were performed on Eu-DPA+5-HIAA under 287nm excitation. Fig.38 As shown in Figure f, the observed signal is positive, which indicates that under the action of the pump light, Eu-DPA+5-HIAA transitions from the ground state to the excited state, and under the action of the detection pulse, the excited state particles further absorb energy and transition to a higher energy level, thereby generating a positive ΔA signal. Fig.38 h. It is worth noting that Eu-DPA+5-HIAA showed no stimulated emission (SE), indicating that no energy transfer from the ligand DPA to the rare earth Eu occurred in this system, further confirming the existence of a blocked energy transfer process. No fluorescence emission of the ligand was observed on the fs time scale, and it was not until the ns scale that the ligand began to fluoresce. This observation is consistent with the results of time-resolved fluorescence spectroscopy (TRES), indicating that in the Eu-DPA+5-HIAA system, the addition of 5-HIAA significantly affected the energy transfer pathway, thereby affecting the entire fluorescence response process.
Claims
1. A method for preparing a water-soluble, highly efficient, luminescent lanthanide complex having multiple hydrogen bonding sites, characterized in that It is carried out in the following steps:
1. dissolving a rare earth salt in dimethylformamide to obtain a metal salt solution; The rare earth salt is EuCl3·6H2O, TbCl3·6H2O, YbCl3·6H2O, NdCl3·6H2O or ErCl3·6H2O; 2. dissolving 2,6-pyridinedicarboxylic acid in dimethylformamide to obtain a 2,6-H2dpa solution; 3. Add 2,6-H2dpa solution to the metal salt solution to obtain a reaction system. Heat the reaction system under stirring conditions, then filter the product under reduced pressure, wash and dry it to obtain a dried solid. Add water to the dried solid, then use an ultrasonic two-dimensional material stripper to treat it until a transparent solution is formed, and finally freeze-dry it to obtain a water-soluble, high-efficiency luminescent lanthanide complex with multiple hydrogen bonding sites.
2. The method for preparing a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites according to claim 1, characterized in that The concentration of the metal salt solution described in step 1 is 0.06 mol / L to 0.07 mol / L.
3. The method for preparing a water-soluble, highly efficient, luminescent lanthanide complex having multiple hydrogen bonding sites according to claim 1, characterized in that The concentration of the 2,6-H2dpa solution described in step 2 is 0.1 mol / L to 0.3 mol / L.
4. The method for preparing a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites according to claim 1, characterized in that The concentration of 2,6-pyridinedicarboxylic acid in the reaction system described in step 3 is 0.05 mol / L to 0.15 mol / L; the concentration of rare earth salt in the reaction system described in step 3 is 0.02 mol / L to 0.04 mol / L.
5. The method for preparing a water-soluble, highly efficient, luminescent lanthanide complex having multiple hydrogen bonding sites according to claim 1, characterized in that In step 3, the reaction system is heated for 1 h to 1.5 h at a stirring speed of 2.5 r / s to 3.5 r / s and a reaction temperature of 140° C. to 160° C.
6. The method for preparing a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites according to claim 1, characterized in that In step three, the product is filtered under reduced pressure using a Buchner funnel, then washed with ethanol, and finally dried at a temperature of 70° C. to 100° C. for 8 h to 10 h.
7. The method for preparing a water-soluble, highly efficient, luminescent lanthanide complex having multiple hydrogen bonding sites according to claim 1, characterized in that The mass ratio of the dried solid described in step 3 to the volume of water is 1 g: (3-5) mL.
8. The method for preparing a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites according to claim 1, characterized in that In step 3, at room temperature, a power of 650 W to 750 W and a frequency of 30 KHz to 40 KHz, an ultrasonic two-dimensional material stripper is used for 3 min to 5 min until a transparent solution is formed.
9. The method for preparing a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites according to claim 1, characterized in that The freeze drying described in step 3 is specifically freeze drying for 10h to 12h under vacuum and a drying temperature of -20°C to -30°C.
10. Use of a water-soluble, highly efficient luminescent lanthanide complex having multiple hydrogen bonding sites as prepared according to claim 1, characterized in that It acts as a luminescent sensor for the carcinoid marker 5-HIAA.
